Adipokines and Arterial Stiffness in Obesity - Ioana Para; Adriana Albu; Mihai D. Porojan (Medicina, 2021)
Adipokines are active molecules with pleiotropic effects produced by adipose tissue and involved in obesity-related metabolic and cardiovascular diseases. Arterial stiffness, which is a consequence of arteriosclerosis, has been shown to be an independent predictor of cardiovascular morbidity and mortality. The pathogenesis of arterial stiffness is complex but incompletely understood. Adipokines dysregulation may induce, by various mechanisms, vascular inflammation, endothelial dysfunction, and vascular remodeling, leading to increased arterial stiffness. This article summarizes literature data regarding adipokine-related pathogenetic mechanisms involved in the development of arterial stiffness, particularly in obesity, as well as the results of clinical and epidemiological studies which investigated the relationship between adipokines and arterial stiffness.